PENGARUH PRODUK DAN TEMPAT TERHADAP TINGKAT KEPUASAN PESERTA PELATIHAN KEWIRAUSAHAAN DAN PENYUSUNAN ANGGARAN BAGI PELAKU UMKM JEMAAT GBKP KELURAHAN KARANG JOANG BALIKPAPAN - Rudy Pudjut Harianto (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2020)
This research aims to analyze the effect product and place toward satisfaction of budgettraining participants for small, micro and medium enterprises on Jemaat GBKP Balikpapan.This research used quantitative and qualitative method with primary data sources and usingnonprobability sampling method with 32 respondents. Data analyse method that used in thisresearch are validity and reliability test then classical assumption test (normality,multicollinierity, heteroscedasticity, autocorrelation) and Multiple Linier Regression Analyse(correlation coeficient, determination coeficient, F test/varians analyse, t test/significantiontest). Accumulatively, coeficient correlation (R) = 0,537 so that it can be said that theindependent variables toward dependent variable in this research can giving the strong enoughcorrelation. Result of Test Varians (F) express the Ho can be accepted because Fcount < Ftable or5,865 < 3,3277. Its meaning that variable of product and place by together did have theinfluence which significant to satisfaction of budget training participants. The result ofsignificantion test could be explained : (1) there are significant effect of product on satisfactionof budget training participants, and (2) there are not significant effect of place on satisfactionof budget training participants.